The effect of temperature on the hydrothermal synthesis of carbonated apatite from calcium carbonate obtained from green mussels shells - Fitriyana, Deni Fajar; Irawan, Agustinus Purna; Bahatmaka, Aldias; Ismail, Rifky; Bayuseno, Athanasius Priharyoto; Muhamadin, Rilo Chandra; Cionita, Tezara; Siregar, Januar Parlaungan; Jehadus, Emilianus; Baskara, Gregorius Dimas; Laksmidewi, Dwinita; da Silva Guterres, Natalino Fonseca (Asian Research Publishing Network, 2023)
Hydroxyapatite (HAp) refers to a bioceramic broadly employed in bone tissue engineering since it has bioactive and osteoconductive properties. The synthesis of HAp will be more economically viable using waste materials because it is cheap, easy to find, and available in large quantities. Therefore, this study aimed to synthesize and characterize HAp from green mussel shells by hydrothermal method at various temperatures. Precipitated calcium carbonate (PCC), made from green mussel shell powder, is employed in this study. Utilizing a hydrothermal reactor for 14 hours at 120°C, 140°C, as well as 160°C, a combination of PCC and (NH4)2HPO4 with a Ca/P molar ratio of 1.67 was synthesized to form HAp. Note that the synthesis findings were categorized using scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FTIR), as well as X-ray diffraction (XRD) tests. Apart from that, the FTIR test showed the formation of HAp in all test variations because the results of –OH, and –PO4 were found. XRD results that have been analyzed using HighScore Plus software show the percentage of weight (%) and crystal size of HAp increases with increasing hydrothermal temperature. Other than that, HAp produced at hydrothermal temperature variations of 160°C has a hexagonal crystal system with a percentage of weight (%) as well as a crystal size of 46.43 nm and 99.3%, whilst the amount of impurity (%) produced is 0.7%. The higher the hydrothermal temperature, the weight percentage (%), and the crystallite size in HAp are getting bigger while the number of impurities gets smaller.